Dynamics and Periodization of Al-Qur’an Interpretation in the Ottoman Empire (1299-1923 AD) - Bahari, Fadhil Achmad Agus; Muslim, Muslim; Al-Kindi, Farhan Afif (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
The interpretation of the Qur'an during the Ottoman Empire is thought to have faced a period of stagnation, attributed to a lack of interpretive literature production. However, recent philological studies suggest a notable flourishing of Quranic interpretation during its golden age. This study aims to challenge this assumption by proposing a hypothesis that the practice of interpreting the Qur'an in the Ottoman Empire was shaped by historical conditions, political turmoil, and the intellectual capabilities of its people. It delves into the dynamics of Quranic interpretation activities, exploring chronological periods during the Ottoman era. Employing descriptive-analytical techniques within a historical context, the study conducts a literature review with primary sources, including Quranic commentary books by Ottoman interpreters, and secondary sources, such as journal articles and books on Quranic interpretation and Ottoman Empire history. The findings reveal that Quranic interpretation during the Ottoman Empire exhibited adaptability to historical changes. The observed dynamics are categorized into three periods: the interaction period, marked by the introduction of classical interpretive works; the culmination period, representing the peak of Quranic interpretation practice; and the decline period, characterized by a weakening tradition due to internal and external challenges faced by the Empire.